Automation of Water Treatment System with pH Sensors, Conductivity Sensors and Turbidity Sensors Based on Microcontroller - Fadhlurrahman, Mitsal Iqbal; Soelistianto, Farida Arinie; Purwandi, Ahmad Wahyu (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
Water is main need for humans. People living around river use river water as consumsion, but majority of urban rivers are polluted. Polluted river water contains dissolved solids, unsTable water pH content and water turbidity. The government provides facilities used by residents to bathe, wash and defecate in residential areas with medium to high density, namely MCK. The MCK is close ± 2 meters close to the polluted river. Solution to this problem requires a water treatment tool that works automatically and can monitor the water content of the water treatment system based on water quality in accordance with PERMENKES No. 32 of 2017 which can monitor dissolved solids, turbidity and water pH. Officers can see the sensor reading process via website containing water quality content. Based on the results of tests carried out over 3 days, average water content in pH sensor was 6.77pH, conductivity sensor was 595.9ppm and tubidity sensor was 13.05NTU. The results of water content for three days are in accordance with standardization. Water treatment system is running well. Quality of Service testing for 3 days with an average delay of 0.0358s and packet loss of 0.48% is categorized as good